Correlation with Adrenal Hormones and Kidney Stone Pathogenesis Biochemical and Immunological Parameters in Human Patients - Aljezani, Hasan Ali Mohamed (Journal of Current and Advance Medical Research, 2025)
Background: Kidney stones are solid deposits that form in the urinary system, especially the kidneys, from chemical substances like salts and minerals. The pathophysiology of stone development involves aldosterone hormones and renin., as biochemical indicators of the kidney's susceptibility to different types of stones. In this study, two types of stones were used in relation to their formation in patients (calcium oxalate and uric acid stones). TNF and IL-17 were also thought to affect stone formation. Significant characteristics like smoking, BMI, and sex were examined. Objective: Assessing hormones in patients with kidney stones of both types (calcium oxalate and uric acid) and their relationship to smoking, body mass index, gender, and immunological indicators like tumor necrosis factor and interleukin-17. Methodology: This case-control study took 98 blood samples from kidney stone patients and healthy people. From May 2022 to December 2022, 68 patients with urinary tract problems, specifically kidney stones, were identified, along with 30 healthy individuals as a control group. Serum was obtained from blood. The samples were categorized as (38) calcium oxalate stone patients, (30) uric acid stone patients, and (30) healthy persons. Vital and immunological parameters were evaluated using ELISA. Results: Patients with calcium oxalate stones differed significantly from smokers (P<0.05), while those with uric acid stones differed significantly from smokers in terms of body mass (P<0.01). Gender index did not differ significantly across groups, but hormones (aldosterone, renin) and immune factors (TNF, IL-17) differed significantly between calcium oxalate and uric acid stones and the healthy group (P<0.01). Conclusion: Hormones affected the production of calcium oxalate and uric acid stones. Aldosterone hormone release increased calcium oxalate stone development, while renin depression increased both forms of stones. Smoking had an effect on uric acid stone patients, and immune indicators like TNF and IL-17 were vital as stone formation increased their blood levels. Journal of Current and Advance Medical Research, July 2024;11(2):102-108